A high therapeutic efficacy of polymeric prodrug nano-assembly for a combination of photodynamic therapy and chemotherapy. (December 2018) - Yi, Xiaoqing; Dai, Jun; Han, Yingyan; Xu, Min; Zhang, Xiaojin; Zhen, Shijie; Zhao, Zujin; Lou, Xiaoding; Xia, Fan
Abstract Combination of photodynamic therapy and chemotherapy has been emerging as a new strategy for cancer treatment. Conventional photosensitizer tends to aggregate in aqueous media, which causes fluorescence quenching, reduces reactive oxygen species (ROS) production, and limits its clinical application to photodynamic therapy. Traditional nanoparticle drug delivery system for chemotherapy also has its disadvantages, such as low drug loading content, drug leakage, and off-target toxicity for normal tissues. Here, we developed a reduction-sensitive co-delivery micelles TB@PMP for combinational therapy, which composed of entrapping a red aggregation-induced emission fluorogen (AIEgen) for photodynamic therapy and PMP that contains a reduction-sensitive paclitaxel polymeric prodrug for chemotherapy. AIEgen photosensitizer illustrates a much improved photostability and ROS production efficiency in aggregate state and PMP loads a high dose of paclitaxel and carries a smart stimuli-triggered drug release property. This co-delivery system provides a better option that replaces AIEgen photosensitizer for cancer diagnosis and therapy. Xiaoqing Yi et al. report a co-drug delivery micelle system that demonstrates a high therapeutic efficacy for cancer. This system shows a much improved drug load, photostability, and production of reactive oxygen species, compared to traditional photosensitizer-loaded nanoparticles.